1994
DOI: 10.1002/cyto.990150212
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genetic changes in Barrett's adenocarcirioma and Barrett's esophagus by DNA in situ hybridization and immunohistochemistry

Abstract: We have investigated the occurrence of chromosomal DNA and cell cycle‐related protein changes in Barrett's epithelium and adenocarcinoma. The presence of numerical chromosomal aberrations was studied by applying nonisotopic in situ hybridization (ISH) with (peri‐)centromeric DNA probes, specific for chromosomes 7, 8, 17, and Y, to routinely processed tissue sections of five cases (4 male, 1 female) of Barrett's adenocarcinoma and adjacent Barrett's epithelium. Cell cycle‐related protein expression was studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 32 publications
(36 reference statements)
3
19
0
1
Order By: Relevance
“…[34][35][36][37][38][39] The studies consistently show an accumulation of chromosomal abnormalities as the histologic changes progress from intestinal metaplasia to dysplasia and carcinoma. 4,[40][41][42][43] Previously reported changes detectable by FISH in esophagectomy specimens suggested that gains of chromosomes 6, 7, 11, and 12 might be among the numerical abnormalities occurring most frequently in the Barrett's esophagus-associated HGD and adenocarcinoma, findings which we have confirmed with the use of endoscopic cytology specimens. 22 Only sparse data are available in the literature regarding the use of FISH on endoscopic brush cytology specimens for biomarker assessment in Barrett's esophagus.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…[34][35][36][37][38][39] The studies consistently show an accumulation of chromosomal abnormalities as the histologic changes progress from intestinal metaplasia to dysplasia and carcinoma. 4,[40][41][42][43] Previously reported changes detectable by FISH in esophagectomy specimens suggested that gains of chromosomes 6, 7, 11, and 12 might be among the numerical abnormalities occurring most frequently in the Barrett's esophagus-associated HGD and adenocarcinoma, findings which we have confirmed with the use of endoscopic cytology specimens. 22 Only sparse data are available in the literature regarding the use of FISH on endoscopic brush cytology specimens for biomarker assessment in Barrett's esophagus.…”
Section: Discussionsupporting
confidence: 73%
“…The loss of cell cycle check point control, which results from this alteration, can lead to asymmetrical chromosome segregation during cell division and subsequent aneuploidy. 40 Mutations of p53 and 17p13.1 loss of heterozygosity have been reported in upto 92 and 100% of esophageal adenocarcinomas. [41][42][43] Our study demonstrates that the genomic loss of the 17p13.1 region (p53 gene) occurs in the majority of the HGD/ adenocarcinoma cases (76%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internal controls (normal prostate glands: 13 cases; BPH: 4 cases; leukocytes: 131 cases; other cells: 5 cases) on the same tissue sections always showed a diploid pattern (van Dekken and Alers, 1993;Krishnadath et al, 1994). T h e number of nuclei with a hyperdiploid spot number (likely artifacts) in these internal controls never exceeded 2.5%.…”
Section: Evaluation Of Ish Resultsmentioning
confidence: 93%
“…15,34,35 But, it remains to clarify its role as a cause or an effect. So far, no specific tumor suppressor genes have been mapped to the Y chromosome and Krishnadath et al, 36 who found no correlation between proliferation rates as detected by Ki-67 and loss of Y chromosome, did not confirm the hypothesis that its loss might confer proliferative advantage. Despite its unclear role as a side effect or a true initiating mechanism, all previous studies described chromo- some Y loss in Barrett's esophagus adjacent to neoplasia.…”
Section: Discussionmentioning
confidence: 93%